Knowledge, attitudes and practices of caregivers of children 0 - 23 months in eastern and central Uganda - Asiimwe, Kamuntu Jacent; Nambooze, Joweria; Ssonko, Wilson George; Kakande, James; Nyanzi, Lilian; Kaddu, Peter (Scientific Research Publishing Inc., 2021)
Introduction: Appropriate feeding and consequently good nutritional status of young children largely depends on their caregivers. Aim: The current study aimed at assessing maternal/caregivers’ current knowledge, attitudes, practices, and beliefs regarding different aspects of infant and young child feeding in Eastern and Central Uganda. Methodology: A cross-sectional survey design with mixed methods employing both qualitative and quantitative methods was used for data collection. Results: The study participants included 556 caregivers and 572 children. Results indicate that most caregivers (77%) were knowledgeable about key infant and young child feeding practices such as breastfeeding, complementary feeding and meal frequency. However, culture and economic hardships were a major barrier to the applicability of this knowledge. Nearly all (98%) children were ever breastfed with 41% having been initiated on breast milk in the first hour after birth and 68% of all the children below 6 months exclusively breastfed. Three percent of the children aged 6 - 23 months were classified as having either Moderate (2%) or Severe (1%) Acute malnutrition. The median birth weight was 3.2 Kgs with nine percent of the children classified as underweight at birth. The majority (78%) of the children consumed foods from at least four food groups however only 44% consumed heme-rich animal flesh food such as meat, poultry, organ meats and fish, 29% consumed milk and milk products while only 11% consumed eggs. The barriers to improved nutritional status and health-seeking behaviour in children from both regions were largely similar. Some of these included cultural practices which prohibit children from eating certain foods and lack of drugs in the health facilities. Lack of male involvement was a key barrier to health-seeking behaviour and the nutritional well-being of children. Males were, however, more knowledgeable about the key childcare practices that are critical to positive outcomes because they listen to radios, have access to social media and usually congregate at bars where this information is disseminated and exchanged. Conclusion: There should be continuous sensitization of mothers on the benefits of breastfeeding with special focus on early initiation and exclusive breastfeeding as well as child feeding practices during illness. To increase protein intake in children 6 - 23 months, interventions aimed at increasing consumption of these vital nutrients such as promotion of nutrition-sensitive agricultural enterprises like rearing of small livestock and chickens should be emphasized. Consumption of these foods is critical, especially during pregnancy and infancy. Finally, male involvement in maternal and child feeding should be encouraged. Keywords Nutritional Status, Knowledge Attitudes and Practices, Breast Feeding, Complementary Feeding, Dietary Diversity, Male Involvement
Article